Classified recall vocabulary in Bengali - Chowdhury, B.C. (My University, 2000)
The Recall Vocabulary in Bengali is prepared to keep in view the needs of the second language learners in Bengali. It is hoped that the learners of Bengali will find this book useful.
Keywords: Bengali